Accessibilité à l'eau potable dans le bassin géographique sud-béninois du fleuve mono : etude comparative entre zone inondable (zi) et zone non i - GADO, RAIMI; SEBO, ERIC; AZONHE, THIERRY HERVÉ S. NICÉPHORE (My University, 2014)
Abundant studies approached the problematic of the access in general to the drinking water in the world and in the developmental countries as Benin in particular. To the benign, this problematic has been landed regularly under the angles of the fashions of provision in water and the quality of water consumed by the populations. However, the question of the access to the drinking water is a lot more complex than it. Indeed, while only approaching the question of the access to the drinking water under the angles of the fashions of provision in water and the quality of water consumed by the populations, the acuteness of the difficulties bound at the access to water is not at all audible. The present survey that is achieved in the basin of the Mono in the South of Benin (geographical space that evolves to the rhythm of the dynamics of the Mono stream with his/her/its corollaries of which most important is the periodic phenomenon of the floodings), is the first of a set of studies that analyzes the question more through the aspects of availability (cover of the basin in points of provision in water (PE), rate of servicing of the populations), of geographical accessibility (geographical position of the PE in relation to the dwellings or to the households, browsed distances and time put to get a stock in water) and of economic value (volumes of water clear soups daily per person, price of the cubic meter to the level of the PE, yearly theoretical budget of consumption of water of the households) of water. Thus, the present survey dedicates itself to the geographical accessibility of the populations of the basin to the drinking water. To succeed the survey, an investigation has been achieved by a sample of 1 168 households gotten from the method of SCHWARTZ (1995). The results reveal deep contrasts in terms of distances browsed to reach water in the basin.
Keywords: basin of the Mono; drinking water; availability; geographical accessibility